1994
DOI: 10.1002/j.1460-2075.1994.tb06648.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential sorting of lysosomal enzymes in mannose 6-phosphate receptor-deficient fibroblasts.

Abstract: In higher eukaryotes, the transport of soluble lysosomal enzymes involves the recognition of their mannose 6‐phosphate signal by two receptors: the cation‐independent mannose 6‐phosphate/insulin‐like growth factor II receptor (CI‐MPR) and the cation‐dependent mannose 6‐phosphate receptor (CD‐MPR). It is not known why these two different proteins are present in most cell types. To investigate their relative function in lysosomal enzyme targeting, we created cell lines that lack either or both MPRs. This was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
141
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(153 citation statements)
references
References 22 publications
12
141
0
Order By: Relevance
“…Acid hydrolase can also reach endolysosomes after endocytosis by the cation-independent MPR. In the absence of UDP-GlcNAc:lysosomal enzyme GlcNAc-1-phosphotransferase (also known as GlcNAc-1-phosphotransferase; hereafter Ptase) (the first enzyme involved in Man-6-P synthesis), or upon knockdown of MPRs, fibroblasts and other cells of mesenchymal origin, as well as acinar secretory cells, missort their acid hydrolases, causing lysosomal dysfunction (Ludwig et al, 1994;Pohlmann et al, 1995;Kornfeld and Sly, 2000;Boonen et al, 2011). However, intriguingly, the aspartic protease cathespin D can still reach lysosomes in several cell types (Rijnboutt et al, 1991;Glickman and Kornfeld, 1993;Dittmer et al, 1999;Pohl et al, 2010;van Meel et al, 2011;Markmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Acid hydrolase can also reach endolysosomes after endocytosis by the cation-independent MPR. In the absence of UDP-GlcNAc:lysosomal enzyme GlcNAc-1-phosphotransferase (also known as GlcNAc-1-phosphotransferase; hereafter Ptase) (the first enzyme involved in Man-6-P synthesis), or upon knockdown of MPRs, fibroblasts and other cells of mesenchymal origin, as well as acinar secretory cells, missort their acid hydrolases, causing lysosomal dysfunction (Ludwig et al, 1994;Pohlmann et al, 1995;Kornfeld and Sly, 2000;Boonen et al, 2011). However, intriguingly, the aspartic protease cathespin D can still reach lysosomes in several cell types (Rijnboutt et al, 1991;Glickman and Kornfeld, 1993;Dittmer et al, 1999;Pohl et al, 2010;van Meel et al, 2011;Markmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in MPR46 and/or M6P/IGF2R have been generated (Köster et al, 1993;Ludwig et al, 1993;Ludwig et al, 1994). Studies on MPR46-and/or M6P/IGF2R-negative fibroblasts have indicated that both receptors are necessary for efficient lysosomal targeting.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Lysosomal sorting via M6P/IGF2R is generally far more efficient than by MPR46, demonstrating that the former is the main lysosomal targeting receptor in mammalian cells. 11,12 However, M6P/IGF2R also binds a variety of other factors that impinge on the proliferation, migration and invasiveness of tumour cells, including insulin-like growth factor II (IGF-II), 13 transforming growth factor b, 14 urokinase-type plasminogen activator receptor 15 and plasminogen. 16 Hence, it is of high relevance that the M6P/IGF2R gene is frequently inactivated in human and animal tumours.…”
mentioning
confidence: 99%